Neuromarketing in the positioning of the hotel sector in Villahermosa, Tabasco - Toledo-Sánchez, Danna P. (2024)
The article describes the level of influence of neuromarketing on the positioning of the hotels in Villahermosa Tabasco; Neuromarketing is a tool that has gained relevance and has become one of the most used by companies in various sectors, one of these is the hotel sector, which is in recovery due to the ravages left by the pandemic. In the development of the research, a quantitative methodology with an explanatory analysis was used; a theoretical framework that includes articles, studies, books, and the web, on the use and importance of neuromarketing in various sectors of the world. The objective of the research was to determine how the application of neuromarketing influences the positioning strategies implemented by hotels in the area, to recognize its importance and current application. The results show that Neuromarketing is a widely used tool currently for attracting and retaining customers through various positioning strategies.